POTENSI BIJI JARAK PAGAR SEBAGAI RODENTISIDA ALAMI - Edo Legianto Pratama; Tuti Heiriyani; Riza Adrianoor Saputra (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[JATROPHA SEED POTENTIAL AS A NATURAL RODENTICIDE]. The controlling of rat's pest attacks often use chemical control that adversely affects non-target animals and leaves a residue for the environment. One of the recommended controls is to use natural rodenticides derived from jatropha seeds and do not harm non-target animals that are environmentally friendly. This research aims to determine the interaction and the best combination of bait mixed with jatropha seeds on the death of Mus musculus, as well as the type of bait and the best dose of jatropha seeds on the death of Mus musculus. The design in this study used a completely randomized design consisting of two factors, the first factor was the bait and the second factor was the dose of jatropha seeds. The results showed that there was an interaction between the type of bait and the dose of jatropha seeds on the amount of feed consumed by Mus musculus. The combination of bait type and dose of jatropha seeds that was best for the mortality of Mus musculus was found in the treatment of rice flour with 3.0 g of jatropha seeds, cornflour with 3.0 g of jatropha seeds, and fish meal with 3.0 g of jatropha seeds. The best dose of jatropha seeds in reducing the bodyweight of Mus musculus, accelerating the time of death, and increasing the percentage of death was 3.0 g of jatropha seeds with an average decrease in body weight of Mus musculus reaching 75%, and the fastest death for five days, and able to kill 100% of Mus musculus.